II,§1,5-II,§1,6
97
thus
nm(A4, ,a) - arg
d`(xz)
+ arg
d`(Rxz )
n n
= nm(14,,a) -
nm(X*a, RA4) + m(X a*, Rya)
= n Inert(X *, RA', R)) mod 4n
by I,§2,(8.2). Then, by the definition of arg Hess [I,§1,(2.1)], to prove
(5.17) it suffices to show that
Inert(q) - tb') = Inert(X*, R)', R)). (5.19)
Proof of (5.19).
Let us write down the equations of R..., RA', and X*:
RA:p = (D .,(x),
R)':p' _ Dx(x'), X*:x" = 0.
The definition of Inert (I,§2,4) makes use of
z E R1.,
z' E RA',
z" E X* such that z + z' + z" = 0.
Define
z = (x, P), z' = (x', P),
z , = W" P");
hence
x+x'=0, x"=0, p+p'+p"=0,
[z",z]=(P",x)=-(P,x>-(P',x>
_ - (cb (x), x> + (b' (x), x> =
2 b'(x) - 2 b(x).
Consequently,
Inert(R), R)', X*) = Inert(O' - 0).
(5.19) follows by I,§2,(4.4) and I,§1,definition 2.3, of the inertia of a form.
6. Formal Differential Operators
Definition 6.1.
Let 0 be an open set in Z. Let
denote the set of
formal functions with vanishing phase
a° = 1
1r
ar
(6.1)
rEN v